Guide to US food laws and regulations - Curtis, Patricia A. (Hoboken, N.J. : John Wiley & Sons Inc., 2013)
For both student food scientists and experienced professionals, a knowledge of U.S. food law is the foundation that supports an understanding of all industry regulation. Based on a popular internet course, Guide to Food Laws and Regulations, 2nd Edition informs students on the significance, range, and background of food laws and gives tools for finding current regulations. This compact resource outlines major U.S. food laws, factors that led to their passage, and explains the role of key agencies like the FDA and FSIS in regulation and enforcement. Students are directed to int.
Includes index.
Print version record and CIP data provided by publisher.
Keywords: Food law and legislation -- United States; LAW -- Administrative Law & Regulatory Practice; Food law and legislation; United States; Electronic books